Effect of different tumbling marination methods and time on the quality characteristics of prepared pork chops - Gao,Tian (2015)
AbstractThe combined effects of tumbling marination methods (Vacuum continuous tumbling marination, CT; Vacuum intermittent tumbling marination, IT) and effective tumbling time (4, 6, 8 and 10 h) on quality characteristics of prepared boneless pork chops were investigated. The results showed that regardless of tumbling time, CT method significantly increased the pH, product yield, cohesiveness, resilience, sensory tenderness and overall flavor (p<0.05) compared with IT method, and CT method also significantly decreased the pressing loss, cooking loss, shear force value (SFV), hardness and chewiness (p<0.05) compared with IT method. With the effective tumbling time increasing from 4 h to 10 h, the product yield and sensory attributes of prepared pork chops increased at first and then decreased, whereas the pressing loss, cooking loss, SFV, hardness and chewiness decreased at first and then increased. Additionally, an interaction between CT method and effective tumbling time was also observed. These results suggested that CT method of 8 h obtained the best quality characteristics of prepared pork chops, which should be adopted.